British Sikh entrepreneurs: Social mobility and transformations over generations. (2nd January 2018) - Dhillon, Jaswinder K.; Thomas, Nest
ABSTRACT: We came with £3 in our pocket but with hard work and Waheguru's kirpa [God's blessing] we are now playing in millions [lakhan wich khailde haan]. The above quote from an 81-year-old Sikh woman encapsulates the essence of the research reported in this article. The study focuses on factors that have contributed to the socio-economic success and relative upward social mobility of British Sikh families. The research develops an original methodology: bilingual-bicultural ethnography, to analyse and document the perspectives and experiences of three generations of Sikh families. The findings focus on family trajectories of Sikh entrepreneurs.